2011
DOI: 10.1021/jm201010e
|View full text |Cite
|
Sign up to set email alerts
|

Myelin Imaging Compound (MIC) Enhanced Magnetic Resonance Imaging of Myelination

Abstract: The vertebrate nervous system is characterized by myelination, a fundamental biological process that protects the axons and facilitates electric pulse transduction. Damage to myelin is considered a major effect of autoimmune diseases such as multiple sclerosis (MS). Currently, therapeutic interventions are focused on protecting myelin integrity and promoting myelin repair. These efforts need to be accompanied by an effective imaging tool that correlates the disease progression with the extent of myelination. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 45 publications
1
17
0
1
Order By: Relevance
“…As a result, researchers rely on a variety of pulse sequences to exploit variations in either proton density and tissue relaxation properties (Johnson et al 2010;McLaren et al 2009;Johnson et al 2012), and/or a limited number of contrast agents. To date the majority of studies have utilized gadolinium-based contrast agents, such as Magnevist® and Pro-Hance®, however Manganese, a functional contrast agent (Koretsky and Silva 2004) (Leergaard et al 2003), and more recently potassium dichromate (Rowland 2011;Zhang et al 2010) and myelin-specific (Frullano et al 2012) contrast agents have also been used.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, researchers rely on a variety of pulse sequences to exploit variations in either proton density and tissue relaxation properties (Johnson et al 2010;McLaren et al 2009;Johnson et al 2012), and/or a limited number of contrast agents. To date the majority of studies have utilized gadolinium-based contrast agents, such as Magnevist® and Pro-Hance®, however Manganese, a functional contrast agent (Koretsky and Silva 2004) (Leergaard et al 2003), and more recently potassium dichromate (Rowland 2011;Zhang et al 2010) and myelin-specific (Frullano et al 2012) contrast agents have also been used.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the synthesis of targeting biomarkers to image neuropathology with MRI is an active area of research because of the current lack of in vivo detection methods. β-Amyloid peptides and myelin are two components that have been investigated as targets [3539]. …”
Section: The Conjugation Strategymentioning
confidence: 99%
“…Wang and coworkers reported myelin-targeted contrast agent 14 (Fig. 2) [38, 39]. Contrast agent 14 contains a coumarine derivative as the targeting unit conjugated to Gd III DOTA, and this agent has a relaxivity of 5.2 mM −1 s −1 (9.4 T, 21 °C, and water).…”
Section: The Conjugation Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Myelin‐specific contrast agents provide a way to augment the lack of specificity when imaging myelin. Myelin‐specific Gd III ‐containing small molecules were reported that are similar in efficiency to nonspecific clinically approved contrast agents . These contrast agents that have longitudinal relaxivity ( r 1 ) of ~5.1 mM –1 s –1 at 1.41 T were able to highlight myelination in MRI via T 1 maps; however, the images acquired with these agents demonstrate the need for contrast agents with higher relaxivity values to produce images of myelinated structures with increased signal‐to‐noise ratios .…”
Section: Introductionmentioning
confidence: 99%